XXIX Expert Advisory Board of the Russian Glaucoma Society, the XII meeting of the International Expert Advisory Board on glaucoma issues - A.V. Seleznev (РМЖ "Клиническая офтальмология")
A.V. Seleznev Ivanovo State Medical Academy, Ivanovo, Russia On December 8, 2018, the XXIX Expert Advisory Board of the Russian Glaucoma Society (RGS), the XII meeting of the International Expert Advisory Board on glaucoma issues was held in Moscow. President of the RGS, Professor E.A. Egorov highlighted that glaucoma maintains a leading position among the causes of irreversible blindness both in Russia and abroad. New approaches to the diagnosis and treatment of this disease, aimed at personalizing strategic and tactical measures, an emergence of new pharmacological preparations and innovative surgical techniques on the market were considered by the Advisory Board. Besides, a separate vector was the unification of these approaches and the development of uniform algorithms by the World Glaucoma Association. About the author: Aleksei V. Seleznev — MD, PhD, Associate Professor of the Department of Otorhinolaryngology and Ophthalmology. Ivanovo State Medical Academy. 8, Sheremetevsky Ave., Ivanovo, 153012, Russian Federation. Contact information: Aleksei V. Seleznev, e-mail:  fellerok.seleznev@yandex.ru. Financial Disclosure: author has no financial or property interest in any material or method mentioned. There is no conflict of interests. Received 20.12.2018.